GLOMUS TUMOUR - Nabi, Ghulam; Farman, A; Shah, S. Humayun (Journal of Ayub Medical College Abbottabad, 1989)
This tumour was first identified by Rossenwasser in 1945. Many names have been suggested, glomus jugulare,1 nonchromaffin paraganglionoma, chemodectoma,3 paragangianoma of site of origin:4 Lack studied six lakh cases of surgical pathology (1966-1975) and found only sixty-nine cases of Head and Neck Paraganglionoma, incidence being 0.012 per cent out of which 8 cases were of jugulotympanic type. 70% cases occurred in women. The median age was 45-50 years. Following is a case report of such a rare tumour.